2018
DOI: 10.1364/oe.26.030202
|View full text |Cite
|
Sign up to set email alerts
|

Sideways adiabaticity: beyond ray optics for slowly varying metasurfaces

Abstract: Optical metasurfaces (subwavelength-patterned surfaces typically described by variable effective surface impedances) are typically modeled by an approximation akin to ray optics: the reflection or transmission of an incident wave at each point of the surface is computed as if the surface were "locally uniform", and then the total field is obtained by summing all of these local scattered fields via a Huygens principle. (Similar approximations are found in scalar diffraction theory and in ray optics for curved s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 47 publications
(151 reference statements)
0
42
0
Order By: Relevance
“…Another interesting direction to explore would be further development of the theory of nearly periodic structures and locally periodic approximations. In a companion work [46], we develop a rigorous theory of slowly varying (nearly uniform) structures, and show that the analogous "locally uniform" approximation appears as the 0th-order term in a convergent series of integral corrections. A corresponding rigorous theory of higher-order corrections to the locally periodic approximation, analogous to coupled-mode expansions for propagation through nearly periodic media [30], along with efficient numerical methods to obtain corrections, is an important goal for the theory of metasurfaces.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another interesting direction to explore would be further development of the theory of nearly periodic structures and locally periodic approximations. In a companion work [46], we develop a rigorous theory of slowly varying (nearly uniform) structures, and show that the analogous "locally uniform" approximation appears as the 0th-order term in a convergent series of integral corrections. A corresponding rigorous theory of higher-order corrections to the locally periodic approximation, analogous to coupled-mode expansions for propagation through nearly periodic media [30], along with efficient numerical methods to obtain corrections, is an important goal for the theory of metasurfaces.…”
Section: Discussionmentioning
confidence: 99%
“…A corresponding rigorous theory of higher-order corrections to the locally periodic approximation, analogous to coupled-mode expansions for propagation through nearly periodic media [30], along with efficient numerical methods to obtain corrections, is an important goal for the theory of metasurfaces. A closely related problem is coupling radiation to and from guided modes by nearly-periodic surfaces, a version of which is solved in [46]. In another paper [46], we have recently shown that similar local approximations can indeed be used to compute both near fields and coupling to guided waves.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If desired, the optimal design can be further refined by improving the LPA wavefront by minimizing a phase error [15] or wavefront error objective [16]. At the same time, deviations from LPA may be mitigated by considering larger metasurfaces where LPA is more appropriate, by including higher-order corrections to LPA [19], or by incorporating optimization constraints designed to enforce the validity of LPA. For example, the optimization process may be augmented with constraints restricting the structural variations between neighboring cells or specifying a bound on the physical residual:…”
Section: Multi-wavelength Focusingmentioning
confidence: 99%
“…In particular, we find that d 1.5a is enough for accurate modeling of many lens designs. (In contrast, there will be other applications such as grating couplers or excitation of surface resonances [23] in which long-range surface propagation is crucial, but such propagation implies a nearly periodic surface in which LPA will be accurate. In this sense, ODA and LPA are complementary.)…”
Section: Introductionmentioning
confidence: 99%